Fiscal hangover - Fitz-Gerald, Keith
The rules of making money have changed-forever With thecollapse of investment banks, trillion-dollar-plus governmentbailouts, and the Dow plunging like a rock, it's never been moreimportant to understand-and actually profit from-the "new rules."Fact is, Fiscal Hangover, will give you an investingblueprint that will allow you to profit from the changing globaleconomy. For the first time in 200 years, American consumers are steppingdown from their position as the driving force behind the world'seconomy. In Fiscal Hangover, Keith Fitz-Gerald analyzes thedeclining power of the American consumer and introduces you to theresulting investment opportunities. Without question, the Americanconsumer and the United States government have provided the rest ofthe world with liquidity in the form of cheap capital and abundantdebt. But in light of recent economic events, the rules of the gamehave changed and that means you must change with them-if you intendon securing your financial future